A system modeling analysis of circular economy and renewable energy integration in manufacturing - Alqahtani, Mohammed F.; Afy-Shararah, Mohamed (Frontiers in Sustainability, 2025)
IntroductionLimited research and knowledge have tackled the facilitators and hindrances contributing to the integration of circular Economy (CE) and renewable energy (RE) in the manufacturing sector. The primary goal of the current investigation is to build a holistic system that explains why and how manufacturers adopt and implement CE and RE integrations.MethodsThe analysis utilized a mixed-methods research design that began with reviewing 107 peer-reviewed articles published between 2018 and 2023 and soliciting 10 experts' opinions through two focus group sessions held in 2024 with stakeholders in the manufacturing sector. The review and focus groups generated a list of 22 facilitators and barriers distributed across six themes: (a) regulations, (b) institutions, (c) stakeholders, (d) finance and economics, (e) infrastructure, and (f) technology. The 22 factors informed the construction of the system model using causal loop diagram (CLD).ResultsThe analysis produced an integration system comprised of 11 feedback loops, indicating the intersectionality and dynamism of CE and RE integration. Network analysis demonstrated that strong government support, technical research and development, human capital technology programs, consultancy services, and cost were the most influential factors in the integration model.DiscussionThe present analysis contributes to the ongoing debate on how CE and RE are integrated into manufacturing facilities to decrease waste at all levels.